Jaringan Literatur tentang Keterlibatan Kerja: Analisis Kolaborasi, Titik Panas, dan Tema-Tema Baru yang Muncul - Nurhamidah Pulungan; Syamsul Bahri; Rahmat Hidayat (Forum Kerjasama Pendidikan Tinggi, 2026)
This study aims to map the development of the literature on work engagement through a bibliometric approach based on network analysis using VOSviewer software. Work involvement is an important concept in human resource management because it is directly related to employee welfare, individual performance, and workforce retention. This study uses scientific publication data taken from the Google Scholar database with an analysis period of 2021-2025. The analysis was carried out with four main approaches, namely publication development analysis, keyword mapping (co-occurrence analysis), cluster-based mapping, and Google Scholar Rank mapping. The results of the study show that the topic of work engagement has increased significantly in the last two decades and has developed into a multidisciplinary field. The keyword mapping resulted in nine main clusters that represent the focus of global research, including supportive leadership, psychological well-being, and green work engagement. Meanwhile, the collaboration analysis shows the dominance of researchers from the Netherlands, Spain, and Canada who act as the center of knowledge networks. The findings also reveal the emergence of new themes such as digital engagement, hybrid work environment, and psychological safety. Overall, the results of this study provide a comprehensive overview of intellectual structures, collaborative relationships, and thematic evolution in work engagement research. These findings are expected to serve as a basis for further research and development of more adaptive and sustainable human resource management strategies.